Implementation of Da'wah Management in Developing the Professionalism of Islamic Religious Educators - Jalim Muslim (Al-Hayat: Journal of Islamic Education, 2022)
This study aims to describe the integration of da'wah methods for preachers and teachers in the learning process. Dakwah is an invitation to humans to the path of Allah SWT to accept and make Islam the factual basis of life guidelines. Every Muslim is a da'i (preacher). This study uses an interpretive paradigm through a qualitative approach and case studies. Research locations in tertiary institutions where apart from the lecturers' duties, are academics and community servants (preachers). Data collection techniques using interviews, observation and documentation. The analysis tool used is the qualitative analysis model of Miles and Huberman data reduction, data display and verification. Checking data validity using triangulation; credibility, transferability, dependability and confirmability. The results of the study revealed that first, the concept of integrating one's abilities which are emulated in a community group, in this case teaching lecturers and preachers, is very, very important to note and can be a reference for other professions that must be more concerned with the primary task as khalifah fil ardh, namely inviting to the truth or proselytizing; second, the integration of da'wah methods for the teaching profession and da'i can be implemented using the wisdom, mauidzah (commemoration) and mujilah (exchange of opinion) plans, and can be carried out to the formulation of the foundations of aqeedah, intellectuality, da'wah strategy, organizational, technocratic and moral strength.